2016
DOI: 10.1128/aac.01556-16
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences and Characterization of Antibiotic-Resistant Bacteria and Genetic Determinants of Hospital Wastewater in a Tropical Country

Abstract: e Wastewater discharged from clinical isolation and general wards at two hospitals in Singapore was examined to determine the emerging trends of antibiotic resistance (AR). We quantified the concentrations of 12 antibiotic compounds by analysis using liquid chromatography-tandem mass spectrometry (LC-MS/MS), antibiotic-resistant bacteria (ARB), the class 1 integrase gene (intI1), and 16 antibiotic resistance genes (ARGs) that confer resistance to 10 different clinically relevant antibiotics. A subset of 119 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 45 publications
10
49
1
Order By: Relevance
“…Here, it was found that E. coli had the highest resistance to the all drugs tested (100%), this could be attributed to the abundance nature of E. coli in environment and its easy adaptability. Similar trend of high resistance pattern of E. coli from hospital sewage was reported [30,33,[43][44]. In this present study, least resistance by Morganella morganii (20%) was observed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Here, it was found that E. coli had the highest resistance to the all drugs tested (100%), this could be attributed to the abundance nature of E. coli in environment and its easy adaptability. Similar trend of high resistance pattern of E. coli from hospital sewage was reported [30,33,[43][44]. In this present study, least resistance by Morganella morganii (20%) was observed.…”
Section: Discussionsupporting
confidence: 90%
“…By implication, discharging such sewage get into large water receiving bodies without proper treatment could further allow dissemination of bacterial resistance isolates. High bacterial counts from hospital sewage and effluents are also reported [33]. Lein et.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The ranking framework accurately identified 95% of all well-known high risk ARG families as Rank I ARGs and expanded the list by 43 unreported Rank I ARG families. We compared our results against a list of 38 ARG families that were reported to have high clinical concern (to cause treatment failure of healthcare associated infections and/or have been wide-spread phylogenetically and geographically) by the WHO and by literature review (highlighted in purple) 17,19,20,22,[38][39][40][41][42][43][44][45][46][47] (Figure 3). For example, we included extended-spectrum beta-lactamases (ESBL) ARGs (i.e., TEM, SHV, and CTX-M), that recently caused the death of fecal microbiota transplantation (FMT) recipients.…”
Section: Test Figures 1b and S2amentioning
confidence: 99%
“…Besides the presence of viable NDM-positive bacteria in wastewater, blaNDM-1 genes were also shown to be present at significant numbers in municipal wastewaters, which include wastewater discharged from hospitals. Untreated hospital wastewater from two hospitals in Singapore contained 2.29 x 10 6 gene copies/mL of blaNDM and 4.08 x 10 7 , 1.25 x 10 6 , and 6.19 x 10 5 gene copies/mL, of genes blaKPC, blaCTX-M, and blaSHV, respectively (Le et al 2016). Another study that monitored blaNDM-1 numbers in raw wastewater entering a WWTP in Saudi Arabia reported 3.4 x 10 4 ± 2.3 x 10 4 copies/m 3 (Mantilla-Calderon et al 2016).…”
Section: New Delhi Metallo-beta-lactamase In Wastewatermentioning
confidence: 99%